Examining Various Interpretations of Grice's Cooperative Principle - Dwi Tirta Syafitri, Yona; Budiarti, Vira; Simamora, Afriyanti; Aprilya, Rizka (Universitas Lancang Kuning, 2019)
This study aims to examine various interpretations of the principle of cooperation. The principle of cooperation (CP) was first proposed by H.P. Grice in a series of lectures given in 1967. Grice's most influential contribution to linguistics was his theory of implicature. He illustrated that communication follows what he calls the Cooperative Principle (CP) and argues that the fundamental assumption we make when we speak is that we try to work together to build meaningful conversations (1975). The principle of Grice's Cooperation has become controversial in pragmatics. The main source of controversy related to CP is that the term